Maternal Mood and Perception of Infant Temperament at Three Months Predict Depressive Symptoms Scores in Mothers of Preterm Infants at Six Months - Kmita, Grazyna; Kiepura, Eliza; Niedźwiecka, Alicja (Frontiers in Psychology, 2022)
Postpartum depression is more prevalent in mothers and fathers of preterm infants compared to parents of full-term infants and may have long-term detrimental consequences for parental mental health and child development. The temperamental profile of an infant has been postulated as one of the important factors associated with parental depressiveness in the first months postpartum. This study aimed to examine the longitudinal relationship between depressive symptoms and perceived infant temperament at 3 months corrected age, and depressive symptoms at 6 months corrected age among mothers and fathers of infants born preterm. We assessed 59 families with infants born before the 34th gestational week using the Edinburgh Postnatal Depression Scale (EDPS) and the Infant Behavior Questionnaire-Revised. We found that mothers’ scores on EPDS and infants’ Orienting/regulation at 3 months corrected age predicted mothers’ EPDS scores at 6 months corrected age. In particular, higher depressive scores were related to higher depressive symptoms at 6 months corrected age, whereas higher infant Orienting/regulation was related to lower depressive symptoms at 6 months corrected age. Due to the low internal consistency of EPDS at 6 months for fathers, we were unable to conduct similar analyses for fathers. Our results point to the importance of considering both early indices of maternal mood as well as mother-reported measures of preterm infant temperament in the attempts to predict levels of maternal depressiveness in later months of an infant’s life. Further studies are urgently needed in order to better understand the associations between depressiveness and infant temperament in fathers, and with more consideration for the severity of the effects of infant prematurity.